Tingkat Kemampuan Motorik Kasar dalam Penerapan Permainan Tradisional Karapan Sapi Siswa Kelas IV SDN Bubutan IV Surabaya - Ahmad Rhilo Pambudi; Alfi Budi Rizkiyati; Alfian Rozaq; Alfiano Yanuar Erviansyah; Alfish Shobri; Heri Wahyudi; Rinda Kuswati (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
Gross motor development is essential for elementary students’ physical growth and learning. Traditional games are a fun and culturally rich method to stimulate gross motor skills. To examine the effectiveness of the Karapan Sapi traditional game in improving gross motor skills among 4th-grade students at SDN Bubutan IV Surabaya. This study employed Classroom Action Research (CAR) in two cycles involving 26 students, using observation, interviews, and documentation for data collection. Initial observations showed most students were in the "Less Skilled" category. After the intervention using the Karapan Sapi game, all students progressed to the "Highly Skilled" category. The Karapan Sapi game enhanced not only physical abilities but also teamwork, student engagement, and appreciation for local culture. The Karapan Sapi traditional game is an effective and enjoyable educational tool to improve elementary students’ gross motor skills through contextual and cultural-based learning.